Association of galectin‐3 with markers of myocardial function, atherosclerosis, and vascular fibrosis in patients with rheumatoid arthritis. Issue 1 (27th November 2018) - Anyfanti, Panagiota; Gkaliagkousi, Eugenia; Gavriilaki, Eleni; Triantafyllou, Areti; Dolgyras, Panagiotis; Galanopoulou, Vasiliki; Aslanidis, Spyros; Douma, Stella
Abstract : Background: Galectin‐3 has emerged as a promising novel biomarker of cardiovascular fibrosis in patients with cardiovascular diseases. Hypothesis: We investigated whether galectin‐3 correlates with markers of vascular fibrosis, subclinical atherosclerosis, and cardiac function in patients with rheumatoid arthritis (RA), a disease accompanied by high cardiovascular risk. Methods: RA and non‐RA individuals underwent applanation tonometry, carotid ultrasound, and impedance cardiography, to obtain markers of arterial stiffness, subclinical atherosclerosis, and myocardial function, respectively. Cardiovascular risk was estimated from the Framingham Heart Study. Serum levels of galectin‐3 were determined by enzyme‐linked immunosorbent assay. Results: Galectin‐3 was elevated in RA patients (n = 85) compared to controls (n = 39), but this difference was no longer significant after adjustment for the presence of cardiovascular comorbidities. In the univariate analysis, galectin‐3 significantly correlated with markers of vascular stiffness (including pulse wave velocity, central blood pressure, central and peripheral pulse pressure, and total arterial compliance); atherosclerosis (carotid intima‐media thickness); myocardial blood flow (cardiac output, stroke volume) and contractibility (acceleration and velocity index); systemic vascular resistance, and estimated cardiovascular risk. Multivariate analysis models revealed an independent association between galectin‐3 and both cardiac output ( β = −0.274, P = 0.039), as well as systemic vascular resistance ( β = 0.266, P = 0.039). Conclusions: In a relatively well‐controlled cohort of RA patients with low‐grade systemic inflammation and long‐standing disease, serum galectin‐3 might be useful as a marker of cardiac function and cardiovascular fibrosis.